The Role of Halal Lifestyle on Investment Decisions – Case Study on Students in the Management Study Program, Universitas Cokroaminoto - Mifta Fitriyana; Retno Kurnianingsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The role of a halal lifestyle is a form of personal awareness in implementing practices following Islamic teachings. This is related to a person's lifestyle in making an investment decision. The purpose of this study is to see how the role of an investor's halal lifestyle in their investment decisions, seen from Islamic financial literacy, and also their financial behavior. This study examines an investor, a student at Cokroaminoto University, who invests in the stock market. This study employs a qualitative approach, utilizing a case study design. The findings of this study indicate that the role of a halal lifestyle, as reflected in Islamic financial literacy and the financial behavior of investors, can influence the decisions made in their investments.